Corporate governance, European bank performance and the financial crisis. Issue 3 (3rd January 2019) - Ayadi, Mohamed A.; Ayadi, Nesrine; Trabelsi, Samir
Abstract : Purpose: This paper aims to analyze the effects of internal and external governance mechanisms on the performance and risk taking of banks from the Euro zone before and after the 2008 financial crisis. Design/methodology/approach: To avoid macroeconomic problems and shocks and because of data availability, the authors select some countries of the Euro zone, namely, France, Belgium, Germany and Finland, during the 2004-2009 period. These countries share similar macroeconomic environments (unemployment, inflation and economic growth rates). All the data relating to the banks are manually drawn from the supervising reports submitted to banks and are available on the banks' websites and/or on that of the AMF website. The banks included in our sample are drawn from the list of European central banks on www.ecb.int Findings: The empirical results show that banks undertake tradeoffs between different governance mechanisms to alleviate the intensity of the agency conflicts between the shareholders and managers. The findings also confirm that internal mechanisms and capital regulations are complementary and significantly impact bank performance. Research limitations/implications: This analysis can be extended through studying the interaction between bondholders' governance and shareholders' governance and their impact on the 2008 financial crisis. Practical implications: The changes in banking governance help banks find a useful and necessary way to avoid ill-considered risks that can cause a systemic risk. Therefore, some conditions should be met so that banking governance can contribute to the economic development. Social implications: Culture and mentality of good banking governance must grow as much as possible through awareness-raising, training, promotion, recognition of performance, enhancing procedure transparency and stability of good banking governance and regulations, strengthening the national capacity to fight against corruption, and preventive mechanisms. Originality/value: This paper complements previous studies, mainly those of Andres and Vallelado (2008) who examine the impact of the components of the board on banking performance and of Laeven and Levine (2009) who estimate the combined effect of regulatory and ownership structure on the risk-taking of each bank.